The “dual nature” of resource misallocation: the impact of the hindrance of capital and the promotion of labor on the competitiveness of enterprise—a case study of corn seed enterprises - Li, Lanlan; Wang, Xiudong (Frontiers in Sustainable Food Systems, 2025)
The seed industry stands as a vital strategic sector critical to a nation’s agricultural security and food sovereignty. Researching the optimization of resource allocation within seed enterprises is pivotal for advancing national food security and agricultural modernization. Utilizing micro-survey data from China’s corn seed enterprises spanning from 2018 to 2022, this paper empirically analyzes the impact and mechanisms of capital resource mismatch and labor resource mismatch on the competitiveness of corn seed enterprises. The findings reveal that: (1) Capital resource mismatch hinders the enhancement of competitiveness among corn seed enterprises, whereas labor resource mismatch boosts their competitiveness. (2) The phenomenon of “financial ownership discrimination” persists, with capital resource mismatch impeding the competitiveness of non-state-owned corn seed enterprises; concurrently, the “incentive” effect of labor resource mismatch is more pronounced among state-owned corn seed enterprises. (3) In comparison to technology-oriented corn seed enterprises, capital resource mismatch has a significant positive influence on the competitiveness of basic corn seed enterprises, whereas labor resource mismatch has a notable negative impact. (4) The dual technical barriers posed by executives and employees alleviate the inhibitory effect of capital resources on the competitiveness of corn seed enterprises but simultaneously impede the promotional effect of labor resource mismatch. (5) In line with the mismatch effects observed at the micro-enterprise level, labor resource mismatch in the macro factor market also demonstrates a significant positive effect on the competitiveness of corn seed enterprises. Our research findings offer a specific business context for enterprise resource allocation strategies, facilitating the efficient operation of the seed industry system and promoting the healthy development of the seed industry.